Effects of mediastinal irradiation upon respiratory function following mastectomy for carcinoma of breast: A five-year follow-up study. Issue 3 (May 1969) - Cudkowicz, L.; Cunningham, M.; Haldane, E. V.
Abstract : A five-year follow-up study of respiratory function in patients with mediastinal irradiation following mastectomy for carcinoma of the breast revealed the following: Physiological dead space diminishes progressively, reaching a maximum decline at 12 months following irradiation. Partial recovery occurs thereafter with a levelling out at about 62% of the pre-radiation level. Pulmonary diffusing capacity also declines rapidly but recovery begins after 18 months and improves to within normal limits by the fifth year of the follow-up. The residual volume immediately increases at the end of irradiation therapy but rapidly and permanently returns to normal. Some increase in alveolar ventilation is apparent throughout and continues for at least four years, presumably as a result of the permanently reduced dead space.